2011
DOI: 10.1086/658941
|View full text |Cite
|
Sign up to set email alerts
|

Highly Resistant Gram-Negative Microorganisms Incidence Density and Occurrence of Nosocomial Transmission (TRIANGLe Study)

Abstract: The nosocomial transmission rate of HR-GNRs was relatively low in all hospitals where well-established transmission-based precautions were used. The incidence density of patients with HR-GNRs was higher in university hospitals, probably due to the patient population and the complexity of the care provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 15 publications
1
27
0
1
Order By: Relevance
“…Of a total of 892 HR-GNR included in the initial study (9), 653 isolates (559 Enterobacteriaceae and 94 nonfermentative Gram-negative rods) were available for further typing. As shown in Table 2, E. coli was the most prevalent species included in this study (296 isolates [53.0%]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of a total of 892 HR-GNR included in the initial study (9), 653 isolates (559 Enterobacteriaceae and 94 nonfermentative Gram-negative rods) were available for further typing. As shown in Table 2, E. coli was the most prevalent species included in this study (296 isolates [53.0%]).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they cannot be used in most clinical laboratories. We tested a commercially available typing method, DiversiLab, on a well-defined collection of HR-GNR from a recent study in Dutch hospitals (9). The objective of this study was to determine the reliability of DiversiLab in comparison with the AFLP typing method for the typing of HR-GNR in a hospital setting.…”
mentioning
confidence: 99%
“…La gran mayoría de los estudios reportan porcentaje de resistencia frente a distintos antimicrobianos en los aislados de los laboratorios. Estudios de incidencia con metodología similar al nuestro se han realizado, pero en general enfocados en una bacteria multi-resistente en particular o una patología puntual y además, considerando a todos los pacientes hospitalizados, sin separar los datos de pacientes críticos, lo que baja considerablemente la incidencia y lo hace poco comparable a nuestros resultados [8][9][10] . Por otra parte, la mayoría son realizados en un solo centro y existen pocos estudios multicéntricos con una red de colaboración que entregue datos a nivel nacional como éste.…”
Section: Discussionunclassified
“…It was observed that the Gram-negative bacilli carriers had a high length of stay (mean: 37.2 days). The prolonged length of stay in health institutions and the antimicrobials used may increase the risk of multidrug-resistant microorganisms acquisition [23] [24].…”
Section: Discussionmentioning
confidence: 99%